Strategi Guru PAI dalam Meningkatkan Keaktifan Pembelajaran melalui Identifikasi Keadaan Siswa (Entry Behavior) Dikelas VII SMP Negeri 25 Kerinci - Abel Yolanda; Alimir Alimir (Lembaga Yasin AlSys, 2026)
Islamic Religious Education (PAI) teachers’ strategies for increasing learning activeness have become a focus of various studies, but research that specifically discusses the use of identifying students’ conditions (entry behavior) as a basis for developing learning strategies at the junior secondary school level remains relatively limited. This study aims to describe PAI teachers’ strategies for increasing learning activeness through the identification of students’ conditions (entry behavior) in Grade VII at SMP Negeri 25 Kerinci. This study used a qualitative approach with a case study design. The research participants consisted of one PAI teacher as the main informant and Grade VII students as supporting informants selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The results show that the teacher identified students’ prior knowledge, interests, motivation, and learning readiness before determining learning strategies. Based on the results of this identification, the teacher applied apperception, question and answer, group discussion, motivation, and reinforcement, thereby increasing students’ activeness in asking questions, discussing, and expressing opinions. The conclusion of this study emphasizes that identifying students’ conditions (entry behavior) plays an important role as the basis for planning adaptive, responsive, and student-centered PAI learning. These findings contribute to strengthening the concept of entry behavior in PAI learning and provide practical implications for teachers in designing more effective learning strategies to increase students’ learning activeness.